Hepatitis E virus and the safety of plasma products: investigations into the reduction capacity of manufacturing processes. Issue 2 (24th September 2015) - Farcet, Maria R.; Lackner, Cornelia; Antoine, Gerhard; Rabel, Philip O.; Wieser, Andreas; Flicker, Andreas; Unger, Ulrike; Modrof, Jens; Kreil, Thomas R.
Abstract : BACKGROUND: Hepatitis E virus (HEV) has been transmitted by transfusion of labile blood products and the occasional detection of HEV RNA in plasma pools indicates that HEV viremic donations might enter the manufacturing process of plasma products. To verify the safety margins of plasma products with respect to HEV, virus reduction steps commonly used in their manufacturing processes were investigated for their effectiveness to reduce HEV. STUDY DESIGN AND METHODS: Detection methods for HEV removal (by reverse transcription quantitative polymerase chain reaction) and inactivation (using an infectivity assay) were established. Immunoaffinity chromatography and 20‐nm virus filtration for Factor (F)VIII, cold ethanol fractionation, and low‐pH treatment for immunoglobulin, heat treatment for human albumin, and 35‐nm nanofiltration for FVIII inhibitor‐bypassing activity (FEIBA) were investigated for their capacity to reduce HEV or the physicochemically similar viruses feline calicivirus (FCV) and hepatitis A virus (HAV). RESULTS: For FVIII, HEV reduction of 3.9 and more than 3.9 log was demonstrated for immunoaffinity chromatography and 20‐nm nanofiltration, respectively, and the cold ethanol fractionation for immunoglobulin removed more than 3.5 log of HEV, to below the limit of detection (LOD). Heat treatment of human albumin inactivated more than 3.1 log of HEV to below the LOD and 35‐nm nanofiltration removed 4.0 log of HEV from the FEIBA intermediate. The results indicated HAV rather than FCV as the more relevant model virus for HEV. CONCLUSION: Substantial HEV reduction during processes commonly used in the manufacturing of plasma products was demonstrated, similar to that previously demonstrated for HAV.